HAMBATAN YANG DIALAMI OLEH MAHASISWA DALAM MENGELOLA KESEHATAN MENTAL SELAMA PANDEMI COVID-19 - Irene Miracle Philian Goszal; Heru Astikasari Setya Murti (Jurnal Inovasi Penelitian, 2023)
During the COVID-19 pandemic, students experienced many changes due to policies to carry out social and physical distancing. This change is then related to students' mental health problems. If mental health problems are not addressed, it will have an impact on their well-being. This study was conducted to find out what are the barriers experienced by students in managing mental health during the COVID-19 pandemic. The research method used is a qualitative method with a phenomenological research design. The participants involved were three students who were recruited by purposive sampling with the following criteria: (1) ages 19-25 years, (2) higher students, and (3) being in Salatiga during the COVID-19 pandemic. Data was collected by semi-structured interviews and then the data were analyzed using descriptive phenomenological analysis (DPA). The results of the analysis show that the barriers experienced by students in managing mental health during the pandemic include: (1) prohibitions on gatherings, (2) changes in activity, and (3) fear of contracting the virus. This study suggests the provision of mental health assistance services that can be easily accessed by students.